2015
DOI: 10.1016/j.matdes.2015.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir processing of a D2 tool steel layer fabricated by laser cladding

Abstract: a b s t r a c tFriction stir processing of a D2 tool steel layer fabricated by laser cladding was carried out to modify its as-cast microstructure. The microstructural evolution in the stir zone was observed and micro-Vickers hardness was measured. A maximum hardness of 857 HV was obtained by friction stir processing at 200 rpm. This value is higher than that of the clad layer when it is subjected to austenitizing heat treatment without friction stir processing. This superior property is attributed to the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…2. In order to clarify the appropriate offset position of the rotation tool, the traveling direction of the tool was 0.61 inclined from the butt surface so that the offset position was varied between À0.7 and 2.0 mm [10,18]. In this study, zero is at the position where the probe plunged into the magnesium plate as it just touches the butt face, and plus is at the position where the probe enters into the steel plate, while minus is at the position where the probe enters into the magnesium plate [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…2. In order to clarify the appropriate offset position of the rotation tool, the traveling direction of the tool was 0.61 inclined from the butt surface so that the offset position was varied between À0.7 and 2.0 mm [10,18]. In this study, zero is at the position where the probe plunged into the magnesium plate as it just touches the butt face, and plus is at the position where the probe enters into the steel plate, while minus is at the position where the probe enters into the magnesium plate [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, during the FSP process, part of the original ferrite phase (including bainite) transformed to the austenite phase, and then transformed to the martensite phase during the subsequent rapid water cooling. Furthermore, dynamic recrystallization of the ferrite and the austenite phases occurred during the FSP process due to the intense plastic deformation, resulting in the ultrafine structure [11][12][13][14][15]. Meanwhile, the original carbides in the bainite phases were dissolved due to the high temperature and severe plastic deformation during FSP, and the carbon atoms diffused into the austensite matrix.…”
Section: Resultsmentioning
confidence: 99%
“…FSP causes significant microstructural refinement, densification, and homogeneity of the processed zone (PZ), thereby improving the properties of the materials. It has been demonstrated that enhanced hardness, strength, fatigue limit, wear and erosion resistance can be obtained in various steels after FSP [9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk nanostructured materials in the form of foils, plates and bars with controlled dimensions were produced via LSEM and thicknesses of up to 2.7 mm (cladding materials are of~0.6 mm thickness) have been achieved [33]. Moreover, morphology produced LSEM principles can be used as benchmarks for other techniques and can be produced by other materials processing techniques such as friction stir processing [54,55]. The results in this work indicate that further parameter optimization during machining, understanding the deformation process during the low cost, efficient and high throughput LSM process, and the correlation with disc materials used for LSM can lead to nanostructured and thermally stable steels where strength and ductility can be optimized.…”
Section: Discussionmentioning
confidence: 99%